2021
DOI: 10.3389/fped.2021.654002
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Development of Hemophagocytic Lymphohistiocytosis in Children With Severe Adenovirus Pneumonia: A Single-Center Retrospective Study

Abstract: Objective: To investigate and analyze the relevant risk factors for hemophagocytic lymphohistiocytosis (HLH) in children with severe adenovirus pneumonia (SAP).Methods: A retrospective study of children with SAP was performed in 30 cases developing HLH and 94 cases not developing HLH from December 2018 to August 2019. The binary logistic regression analysis was used to identify risk factors that were significantly associated with the development of HLH after the univariate analysis, and the receiver operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Thus, the present study was partially consistent with the previous study, although it did not cover so many lipid metabolic markers and did not distinguish pneumonia into common and severe groups. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the present study was partially consistent with the previous study, although it did not cover so many lipid metabolic markers and did not distinguish pneumonia into common and severe groups. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies believed that the increased levels of some lipid metabolic markers such as triglycerides may worsen the prognosis of childhood pneumonia. 8 Others suggested that cholesterol metabolism and the elevated levels of several apolipoproteins may have a protective effect on the disease. 9 , 10 So, a firmed conclusion has not been drawn until then.…”
Section: Introductionmentioning
confidence: 99%
“…Primary HLH is caused by mutations in genes such as PFR1, STX11, and STXBP2, which encode perforin or proteins involved in cytotoxic lymphocyte degranulation ( 3 ). Secondary HLH can be triggered by infections, including Epstein-Barr viruses and adenoviruses ( 4 , 5 ). Rheumatic diseases can also induce secondary HLH, including systemic juvenile idiopathic arthritis (sJIA) and KD ( 2 , 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 80% of adenovirus pneumonia cases occur in children under the age of four, especially infants and young children <2 years old (2). Adenovirus pneumonia can develop in acute respiratory distress syndrome, critically ill patients with respiratory failure, toxic encephalopathy, hemophagocytic lymphohistiocytosis, postinfectious bronchiolitis obliterans (PIBO), and even death, and is an important cause of infant death and disability (3)(4)(5)(6). Adenovirus is highly contagious in schools, hospitals, and other highly enclosed areas, and epidemics in crowded environments can occur (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are currently no predictive methods for severe adenovirus pneumonia. In some studies, the results were complications from severe adenovirus pneumonia rather than predictors (3,5,6). Early and accurate identification, treatment, and prognosis of children with adenovirus pneumonia have positive significance.…”
Section: Introductionmentioning
confidence: 99%